Recent Strategies to Address Hypoxic Tumor Environments in Photodynamic Therapy - Yuyin Du; Jianhua Han; Feiyang Jin; Yongzhong Du (MDPI AG, 2022)
Photodynamic therapy (PDT) has become a promising method of cancer treatment due to its unique properties, such as noninvasiveness and low toxicity. The efficacy of PDT is, however, significantly reduced by the hypoxia tumor environments, because PDT involves the generation of reactive oxygen species (ROS), which requires the great consumption of oxygen. Moreover, the consumption of oxygen caused by PDT would further exacerbate the hypoxia condition, which leads to angiogenesis, invasion of tumors to other parts, and metastasis. Therefore, many research studies have been conducted to design nanoplatforms that can alleviate tumor hypoxia and enhance PDT. Herein, the recent progress on strategies for overcoming tumor hypoxia is reviewed, including the direct transport of oxygen to the tumor site by O2 carriers, the in situ generation of oxygen by decomposition of oxygen-containing compounds, reduced O2 consumption, as well as the regulation of tumor microenvironments. Limitations and future perspectives of these technologies to improve PDT are also discussed.